A Numerical Model of Steam Pipeline. (2016) - Taler, Dawid; Kaczmarski, Karol
Abstract: The aim of this study is to develop a numerical model of transient pipeline operations. The finite volume method (FVM) will be used to solved the energy conservation equations for the pipeline wall and steam. The steam temperature, the temperature of the pipeline wall and thermal stresses can be calculated using the numerical model developed in the paper. This model will be used to simulate the operation of the pipeline during start-up, load changes or shut-down of the boiler.